Changes in Drop and Repeated Jump Ground Reaction Forces After a 10-Week Offseason Strength and Conditioning Program in Division I American Football Players - Zachary Gillen; Reuben Burch; David Saucier; Lesley Strawderman; Tony Luczak; Anthony Piroli; Adam Petway; Ted Rath (International Journal of Strength and Conditioning)
The purpose of this study was to examine changes in ground reaction forces during drop jumps (DJs) and repeated jumps (RJs) across a 10-week offseason strength and conditioning program in collegiate Division I American football players. Twenty-two NCAA Division I American football players were recruited for this study, however, a total of n = 19 subjects (mean ± 95% confidence interval, height=186.83±2.66 cm, body mass=102.73±8.79 cm) completed the study. Subjects visited the laboratory twice, once for pre- and once for post-offseason testing. Subjects performed DJs and RJs during each visit. The DJ was performed off a 30 cm box. The RJ protocol consisted of four consecutive jumps. Ground reaction forces were collected during all jumps. Dependent samples t-tests compared changes in DJ metrics, while repeated measures analyses of variance compared changes in RJ metrics. For the DJ, peak braking power, peak propulsive power, mean propulsive force, and jump height increased (p≤0.027, d≥0.552). For jump 1 of the RJ, peak braking power increased (p=0.005, d=0.733). For all jumps of the RJ, peak propulsive power, mean propulsive force, jump height, and reactive strength index increased (p≤0.049, η2≥0.134). This study demonstrated that DJ and RJ performance increased in 10-weeks of strength and conditioning training. Strength and conditioning coaches may benefit from including DJ and RJ assessments to monitor the effectiveness of the strength and conditioning program.